Financial Impacts from Assignment of Supply and Distribution of Subsidized Fuel in PT Pertamina (PERSERO) - Asep Darmansyah; Yezsa Bella Nugroho; Tuntun Salamatun Zen (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The Indonesian government has been subsidizing fuel to control inflation and stabilize the economy. Although Presidential Regulation 43/2018 mandates fuel compensation, the lack of technical regulations regarding budget allocation and monitoring has led to fuel compensation being classified as long-term receivables. To address this issue, the government issued PMK No. 227 of 2019, providing certainty for Pertamina to bill and collect payments. This regulation affirms the government's commitment to pay Pertamina, as outlined in the reconciliation records between the Ministry of Finance and the company. Internal and external analyses were conducted to understand Pertamina's business challenges, including reviews of financial statements and PESTEL analysis. The lack of regulatory clarity has resulted in negative cash flows and decreased profits for Pertamina. However, the issuance of PMK 227 has facilitated financial recovery, which is expected to enhance Pertamina's profits and increase tax and dividend contributions to the government.